The Income Burden of Capital Taxes - Kaldor, Nicholas (Review of Economic Studies, 1942)
The Income Burden of Capital Taxes Get access Nicholas Kaldor Nicholas Kaldor London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 9, Issue 2, Summer 1942, Pages 138–157, https://doi.org/10.2307/2967666 Published: 01 July 1942